Clinical features and prognosis of patients with acute aortic dissection in China. (April 2017) - Zhao, Lujing; Chai, Yanfen; Li, Zhigang
Objective: To evaluate the clinical features, risk factors, and prognostic significance of different Stanford types of acute aortic dissection (AAD). Methods: We retrospectively analyzed the clinical data and prognostic predictors in 105 patients with AAD (37 with Stanford type A and 68 with Stanford type B) at Tianjin Medical University General Hospital and Tianjin 4th Central Hospital from January 2014 to November 2015. Results: Patients with Marfan syndrome and bicuspid aortic valve constituted 24.3% and 8.1%, respectively, of patients with type A AAD; these proportions were significantly higher than those of patients with type B AAD (7.4% and 0.0%, respectively). The proportion of iatrogenic causes of type A AAD (8.1%) was significantly higher than that of type B AAD (0.0%). Computed tomography angiography showed that the proportion of involvement of the aortic arch and pericardial effusion (86.5% and 18.9%, respectively) in patients with type A AAD were higher than those in patients with type B AAD (23.5% and 5.9%, respectively). Endovascular treatment was performed in a higher proportion of patients with type B than A AAD (70.6% vs. 5.4%, respectively). Conclusion: Systolic blood pressure, pericardial effusion, periaortic hematoma, conservative treatment, and open surgery were independent predictors of increased mortality in patients with AAD.